Regulatory and legal provision of forensic engineering and technical examinations - Bohdaniuk I. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького, 2023)
Purpose. Development of theoretical provisions and practical recommendations on the generalization of legal support for forensic engineering and technical examinations. The methodology provides for a theoretical generalization of the existing normative legal acts related to the conduct of forensic examinations, in general, and engineering and technical examinations, in particular, as well as the formulation of relevant conclusions and recommendations. Methods. The research used a system of general scientific methods, namely theoretical generalization, comparison, system analysis and formalization. Results. The article is devoted to the current problems of the inconsistency of the regulatory and legal provision of forensic examination with the branch legislation regulating narrowly focused issues of certain types of research. It was determined that in order to regulate the activities of experts, it is necessary to implement unified approaches to conducting research that will take into account the peculiarities of conducting each separate type of forensic examination. It is noted that in order to improve regulatory legal acts on forensic expertise, it is advisable to adapt them to European legislation, and the creation of methods of expert research for all forensic institutions should take into account the accreditation features of international quality standards. Originality. In the process of research, it was found that the generalization of the regulatory and legal provision of engineering and technical expertise (on the example of railway transport expertise) is a necessary condition for stable (unchanging) legal regulation of the process of conducting expertise, which, in turn, will increase the efficiency of the work of judicial entities expert activity in the country. Practical significance. The results of the research can be used in the scientific research field, rule-making activities, expert practice and the educational process.